THE GEOMETRICAL FACTORS OF A NAVIGATIONAL SYSTEM - Banachowicz , Andrzej; Wolski, Adam (Problems of Informatization and Management, 2021)
The modem process of navigation is described in four-dimensional space in terms of the physical space - three geometrical dimensions plus time. Consequently, a description and analysis of navigational positionig system accuracy should be performed in the space of the same dimensions. It is particularly important when navigational pseudorange satellite systems are used. These systems, from the point of view of measured navigational parameters analysis, have spatial-time structure. The classical concepts of navigational geometry in two dimensions need to be extended to at least four dimensions.